Northwest passage: Northern Athabaskan copulas and auxiliaries - Welch, Nicholas (2008)
In the Northern Athabaskan languages Tlicho Yatiì, Dene and Dene Dzage, copulas and auxiliary verbs are based on reflexes of two Proto-Athabaskan roots, *-LII and *-T’E’. I propose that in the first two languages, copulas with nominal complements show distributional differences that derive from a stage-/individual-level predicate distinction, and that historically, this distinction in the proto-language motivated the development of auxiliaries marking tense/aspect/mode distinctions solely from the copulas based on *-LII. Further, I propose that subsequent to this development, the original stage-/individual-level predicate distinction between the copulas disappeared in Dene Dzage, leaving the TAM markers as evidence of its historical existence. I provide support for these contentions with data from fieldwork in Tlicho Yatiì and from textual sources in all three languages, grounding the work in current theories of syntax and of temporal grammar.